Model of Imposed Adaptation in Childhood Learning Environments - Application to Autism. A precarious game of developmental Jenga - V. Spielmann; L. Porter (Moscow State University of Psychology and Education, 2019)
Academic and social expectations place ever-increasing stressors on young children. The failings of our academic system to address these concerns greatly impact the general population but may be even more harmful for children on the autism spectrum, who are shown to have significantly higher rates of anxiety, depression, and suicide in later life. The relational and ecological demands indiscriminately placed on autistic children to achieve one-size-fits-all academic learning goals is examined in this paper, along with current evidence exploring the risks faced by autistic youth. Sensory Integration theory posits that brain development and function are driven by actions of the environment upon an organism, and correspondingly the reactions of that same organism on the environment. This notion, an important principle of pediatric occupational therapy, fits within a dynamic systems approach to child development, where environment, relationship, neurobiology and genetics co-act and self-organize through dynamically sustained states. An idea foundational to the proposed model in this paper. We will explore this model using the analogy of Jenga towers to discuss some of the hazards that a reductionist approach to education pose to child development. Finally, questions are asked regarding the implications of these adaptive responses from the perspective of dynamic systems theory.